1997
DOI: 10.1111/j.1540-5915.1997.tb01322.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Innovation Characteristics and Perceived Voluntariness in the Acceptance of Information Technologies

Abstract: The often paradoxical relationship between investment in information technology and gains in productivity has recently been attributed to a lack of user acceptance of information technology innovations. Diverse streams of research have attempted to explain and predict user acceptance of new information technologies. A common theme underlying these various research streams is the inclusion of the perceived characteristics of an innovation as key independent variables. Furthermore, prior research has utilized di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

49
745
11
21

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,195 publications
(826 citation statements)
references
References 27 publications
49
745
11
21
Order By: Relevance
“…For academic staff, the path coefficient between effort expectancy and behavioural intentions showed a weak relationship that was nonsignificant. The latter finding possibly demonstrates the theory that individuals' behavioural intentions become insignificant with increased experience or sustained usage (Agarwal andPrasad 1997: 570, Thompson, Higgins andHowell 1991: 140). The moderating effect of gender provided the first inconclusive result in the student sample, with a significant interaction found through Hayes' (2013) PROCESS analysis, and an insignificant effect observed through bootstrapping in SmartPLS.…”
Section: Effort Expectancy (Ee)mentioning
confidence: 75%
“…For academic staff, the path coefficient between effort expectancy and behavioural intentions showed a weak relationship that was nonsignificant. The latter finding possibly demonstrates the theory that individuals' behavioural intentions become insignificant with increased experience or sustained usage (Agarwal andPrasad 1997: 570, Thompson, Higgins andHowell 1991: 140). The moderating effect of gender provided the first inconclusive result in the student sample, with a significant interaction found through Hayes' (2013) PROCESS analysis, and an insignificant effect observed through bootstrapping in SmartPLS.…”
Section: Effort Expectancy (Ee)mentioning
confidence: 75%
“…Although based upon the Moore and Benbasat (1991) study, which was not about acceptance per se (the paper focused on "adopters" versus "non-adopters"), researchers subsequently began to compare the TAM to PCI models (Plouffe et al 2001;Chin, et al 2002), with some researchers concluding that the diffusion of innovations theory and the TAM are linked (Gagliardi and Compeau 1995). For example, Agarwal and Prasad (1997), using the PCI model as a theoretical lens, concluded that: "The results for current usage suggest that, for this sample, the innovation characteristics of visibility, compatibility, and trialability are relevant in explaining acceptance. "…”
Section: Introductionmentioning
confidence: 99%
“…Consumer innovativeness refers to a general tendency to search, collect, and distribute novel or original experience ahead of the times (Agarwal & Prasad, 1997;Im, Bayus, & Mason, 2003). Social information needs presuppose such a risk-taking propensity, and this fosters a greater level of advertising awareness.…”
Section: Media Appraisalsmentioning
confidence: 99%